Getting the most out of trade in Estonia - Smidova, Zuzana (OECD Economics Department Working Papers, 2017)
Estonia is highly integrated into the global trade system: it exports approximately 80% of GDP and around half of domestic employment is sustained by foreign demand. Given that international trade and foreign direct investment are considered as major channels of technology diffusion and productivity growth, this bodes well for reviving income convergence. To capitalize on the country's high trade intensity, policymakers need to remove remaining trade barriers and improve policies fostering knowledge diffusion as well as talent retention and attraction. At the same time, to ensure that benefits of more trade are shared across the population, the social safety net should be bolstered, and participation in upskilling programmes and their labour-market relevance increased. This Working Paper relates to the 2017 OECD Economic Survey of New Zealand (www.oecd.org/eco/surveys/economic-survey-estonia.htm)